Glibenclamide targets MDH2 to relieve aging phenotypes through metabolism-regulated epigenetic modification - Zhifan Mao; Wenwen Liu; Rong Zou; Ling Sun; Shuman Huang; Lingyu Wu; Liru Chen; Jiale Wu; Shijie Lu; Zhouzhi Song; Xie Li; Yunyuan Huang; et al. (Signal Transduction and Targeted Therapy)
Abstract Mitochondrial metabolism-regulated epigenetic modification is a driving force of aging and a promising target for therapeutic intervention. Mitochondrial malate dehydrogenase (MDH2), an enzyme in the TCA cycle, was identified as an anti-aging target through activity-based protein profiling in present study. The expression level of MDH2 was positively correlated with the cellular senescence in Mdh2 knockdown or overexpression fibroblasts. Glibenclamide (Gli), a classic anti-glycemic drug, was found to inhibit the activity of MDH2 and relieve fibroblast senescence in an MDH2-dependent manner. The anti-aging effects of Gli were also further validated in vivo, as it extended the lifespan and reduced the frailty index of naturally aged mice. Liver specific Mdh2 knockdown eliminated Gli’s beneficial effects in naturally aged mice, reducing p16INK4a expression and hepatic fibrosis. Mechanistically, MDH2 inhibition or knockdown disrupted central carbon metabolism, then enhanced the methionine cycle flux, and subsequently promoted histone methylation. Notably, the tri-methylation of H3K27, identified as a crucial methylation site in reversing cellular senescence, was significantly elevated in hepatic tissues of naturally aged mice with Mdh2 knockdown. Taken together, these findings reveal that MDH2 inhibition or knockdown delays the aging process through metabolic-epigenetic regulation. Our research not only identified MDH2 as a potential therapeutic target and Gli as a lead compound for anti-aging drug development, but also shed light on the intricate interplay of metabolism and epigenetic modifications in aging.